Potassium silica nanostructure improved growth and nutrient uptake of sorghum plants subjected to drought stress - Alharbi, Khadiga; Alnusairi, Ghalia S. H.; Alnusaire, Taghreed S.; Alghanem, Suliman M. S.; Alsudays, Ibtisam Mohammed; Alaklabi, Abdullah; Soliman, Mona H. (Frontiers in Plant Science, 2024)
Recent advancements in nanotechnology present promising opportunities for enhancing crop resilience in adverse environmental conditions. In this study, we conducted a factorial experiment to investigate the influence of potassium nanosilicate (PNS) on sorghum plants exposed to varying degrees of drought stress A randomized complete block design with three replications was employed to subject the sorghum plants to different drought conditions. The three levels of stress were designated as non-stress (NS at -0.03 MPa), moderate stress (MD at -0.6 MPa), and severe stress (SD at -1.2 MPa). The plants were administered PNS at concentrations of 0 mM (control), 3.6 mM Si, and 7.2 mM Si. As drought stress intensified, we observed significant reductions in multiple plant parameters, including height, fresh weight, dry weight, leaf number, stem diameter, cluster length, seed weight, and nutrient uptake, with the most pronounced effects observed under SD conditions. Interestingly, nitrogen (N) and potassium (K) levels exhibited an increase under drought stress and PNS application, peaking at MD, alongside Si concentrations. Notably, PNS application facilitated enhanced nutrient uptake, particularly evident in the significant increase in nitrogen concentration observed at 3.6 mM PNS. Furthermore, the application of PNS significantly enhanced the fresh weight and nutrient concentrations (notably K and Si) in sorghum seeds under drought stress, despite varying statistical significance for other nutrients. These findings shed light on the mechanisms through which PNS exerts beneficial effects on plant performance under drought stress. By elucidating the complex interactions between PNS application, drought stress, and plant physiology, this study contributes significantly to the development of sustainable agricultural practices aimed at bolstering crop resilience and productivity in water-limited environments.